Pressure of intraoesophageal varices assessed by fine needle puncture: its relation to endoscopic signs and severity of liver disease in patients with cirrhosis. Issue 2 (February 1989) - Kleber, G; Sauerbruch, T; Fischer, G; Paumgartner, G
Abstract : In 40 patients with cirrhosis and oesophageal varices transmural variceal pressure was assessed endoscopically by fine needle puncture and related to endoscopic signs as well as to the severity of liver disease. Transmural pressure was significantly (p less than 0.01) higher in the presence of a red colour sign (26.7 (7.8) cm H2O) than in its absence (19.1 (6.6) cm H2O). Transmural pressure, however, was not significantly related to diameter or number of varices (diameter greater than 5 mm: 23.7 (8.4), diameter less than or equal to 5 mm: 22.2 (7.9) cm H2O; number greater than 3: 23.2 (8.0), number less than or equal to 3: 22.2 (7.8) cm H2O). The Child status (Child A: 23.9 (8.0), Child B/C: 21.3 (8.1) cm H2O) and individual Child-Pugh parameters including ascites (ascites present: 23.2 (8.3) cm H2O ascites absent: 22.8 (8.1) cm H2O) were not significantly related to transmural variceal pressure. We conclude that the endoscopic visibility of a red colour sign on the varices is associated with a high transmural oesophageal variceal pressure. Our results favour the hypothesis that variceal pressure may be of major importance for the development of the red colour sign.